Effectiveness of Budget Planning in the Regional Financial Management Information System Application Program - Acmad Taryono; Ismanudin; Mulyati Kartini (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
This study aims to determine the effectiveness of budget planning in the Regional Financial Management Information System (SIMDA) Application Program at the Public Works and Spatial Planning (PUPR) Office of Indramayu Regency. The problem is that the effectiveness of budget planning in the SIMDA Application Program at the PUPR Office of Indramayu Regency appears to be less than optimal. The research method used is a descriptive research method with a case study approach in qualitative research. Key informants were selected based on specific considerations and an understanding of the research problem. Data collection used field study techniques including interviews, documentation, and observation. Data analysis used qualitative analysis techniques. The results of this study indicate that the effectiveness of budget planning in the SIMDA Application Program at the PUPR Office of Indramayu Regency, analyzed based on the following dimensions of effectiveness: (1) Productivity, (2) Efficiency, (3) Flexibility, and (4) Satisfaction, indicates that activity implementation has been quite good. Although there are still internal and external obstacles, these can be effectively addressed by the Agency elements.